2017
DOI: 10.1007/s00402-017-2701-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of type B pelvic fracture using anterior subcutaneous internal fixator with triple pedicle screws: a new surgical technique

Abstract: The use of ASIF/TPS with triple pedicle screws could be a reasonable option for the treatment of type B unstable pelvic fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The anterior subcutaneous pelvic fixator (INFIX) has formerly been described as a treatment option for unstable pelvic ring fractures and biomechanical studies reveal a superior stability of the INFIX compared to a supraacetabular external fixator [6]. Clinical data show that the stability and the clinical outcome of patients with pelvic ring fracture treated with an INFIX (or INFIX with three screws) is sufficient compared to standard open plate osteosynthesis [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anterior subcutaneous pelvic fixator (INFIX) has formerly been described as a treatment option for unstable pelvic ring fractures and biomechanical studies reveal a superior stability of the INFIX compared to a supraacetabular external fixator [6]. Clinical data show that the stability and the clinical outcome of patients with pelvic ring fracture treated with an INFIX (or INFIX with three screws) is sufficient compared to standard open plate osteosynthesis [7].…”
Section: Introductionmentioning
confidence: 99%
“…The configuration providing optimal stability when using the INFIX is debatable. A very limited number of papers demonstrated that it might be useful to add a third screw next to the pubic symphysis [7]. Another option to improve stability while reducing the risk of nerve damage on the contralateral side could be the connection between the unilateral supraacetabular screw with two screws on both side of the pubic symphysis.…”
Section: Introductionmentioning
confidence: 99%
“…INFIX refers to a series of internal fixators which can indirectly reduce and fix pelvic anterior ring injuries with the advantages of short operation time, less intraoperative bleeding, and low infection rates. [ 19 21 ] However, this fixation is not our preference because it only provides the same mechanical strength as an external fixator, which is not enough stability, [ 22 ] and has complications, such as an increased risk of lateral femoral cutaneous nerve injury, painful implant impingement, and femoral nerve palsy caused by connecting rod compression. [ 23 25 ] Comparisons of the fixation strength between the reconstruction plate and the cannulated screw are inconsistent in different mechanical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [16] compared INFIX to open reduction and internal fixation in Type B (Tile classification) pelvic fractures and found the INFIX superior in operation time, length of hospital stay as well as in clinical and radiological 6-month follow-up. However, no subjective questionnaires were given to the patient.…”
Section: Discussionmentioning
confidence: 99%